Pre-diagnosis Cruciferous Vegetables and Isothiocyanates Intake and Ovarian Cancer Survival: A Prospective Cohort Study - Wei, Yi-Fan; Hao, Ying-Ying; Gao, Song; Li, Xiu-Qin; Liu, Fang-Hua; Wen, Zhao-Yan; Wang, Han-Yuan; Zhang, Shuang; Yan, Shi; Luan, Meng; Zhao, Yu-Hong; Gong, Ting-Ting; et al. (Frontiers in Nutrition, 2021)
Abstract Background: The associations of the consumption of cruciferous vegetables (CVs) and their bioactive components, isothiocyanates (ITCs), with ovarian cancer (OC) mortality have been unclear, owing to limited studies and inconsistent findings. To date, no studies have evaluated these associations among Chinese patients with OC. This study aims to provide more evidence indicating the relationships of pre-diagnosis CVs and ITC intake with OC survival. Methods: We examined the associations of pre-diagnosis CV and ITC intake with OC mortality in a hospital-based cohort (n = 853) of Chinese patients with epithelial OC between 2015 and 2020. Pre-diagnosis dietary information was evaluated with a validated food frequency questionnaire. Deaths were ascertained until March 31, 2021 via medical records. The associations were examined with the Cox proportional hazards model, adjusted for potential confounders, and stratified by menopausal status, residual lesions, histological type, and body mass index (BMI). Results: During a median follow-up of 31.2 months (interquartile: 20.0–46.9 months), we observed 130 deaths. The highest tertile of total CV intake was associated with better survival than the lowest tertile intake (hazard ratio (HR) = 0.57, 95% confidence interval (CI) = 0.33–0.98, p trend < 0.05). In addition, greater intake of ITCs from CVs was associated with better survival (HR T3 VS. T1 = 0.59, 95% CI = 0.36–0.99, p trend = 0.06). Significant inverse associations were also observed for subgroup analyses stratified by menopausal status, residual lesions, histological type, and BMI, although not all associations showed statistical significance. Conclusion: Increasing pre-diagnosis consumption of CVs and ITCs was strongly associated with better survival in patients with OC.